Role of Competitive Service Agility in Improving the Relationship between Market Orientation and Marketing Performance - Saptianing - Saptianing; Andi - Setiawan; Riyadi - Riyadi; Suwardi - Suwardi; Nanang Adie Setyawan (Admisi dan Bisnis, 2022)
This study aims to analyze the relationship between market orientation, competitive service agility, social selling activities, and marketing performance. This study makes several contributions to the literature on competitive service agility and social selling activities as the key to marketing performance. The number of respondents analyzed were 168 online driver service actors in Semarang, Central Java. The model approach uses Structural Equation Modeling with AMOS 26.0. This study makes a major contribution that market orientation has a positive influence on competitive service agility. It was also found that competitive service agility has an influence on social selling activities and marketing performance. Finally, regarding mediation analysis, this study confirms that competitive service agility and social selling activities each mediate the effect on marketing performance. Online driver service actors and service providers must also carry out an effective and efficient joint value creation process so that service products can move more agilely and dynamically, so that marketing performance can increase sustainably